1-6(2x-3)=-2

Simple and best practice solution for 1-6(2x-3)=-2 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 1-6(2x-3)=-2 equation:


Simplifying
1 + -6(2x + -3) = -2

Reorder the terms:
1 + -6(-3 + 2x) = -2
1 + (-3 * -6 + 2x * -6) = -2
1 + (18 + -12x) = -2

Combine like terms: 1 + 18 = 19
19 + -12x = -2

Solving
19 + -12x = -2

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-19' to each side of the equation.
19 + -19 + -12x = -2 + -19

Combine like terms: 19 + -19 = 0
0 + -12x = -2 + -19
-12x = -2 + -19

Combine like terms: -2 + -19 = -21
-12x = -21

Divide each side by '-12'.
x = 1.75

Simplifying
x = 1.75

See similar equations:

| 5-2(x+2)=9 | | 15x^5+11x^3-14x=0 | | 2x=-32-5(4x-2) | | 5-3(x+2)=9 | | 6(1-2n)=-2(n-2) | | x=y+1-4 | | (9x-8)+(10x+10)= | | Y=x+1-4 | | 4x^2-6x-10-mx-m=0 | | 2.5+10=1.5+17 | | 5x-2(2x+2)=-6 | | 9b-4=1+6(b+11) | | sqrt(6+x)*sqrt(4-x)=3 | | 10+-2z=-30 | | 11x-5=60 | | 5m-4=3m+12 | | w^3+5w^2+-23w-3= | | -2=-9-2(-2x+1) | | -7f+-31=53 | | X^3-2x+21=0 | | 20+-10c=100 | | 2b+a=5 | | 2,711/9= | | 0.9=0.8+x-0.8x | | (-4x)(-2x^2)= | | x-21=2x+3 | | (w-3)(w^2+8w+1)= | | 7(x+6)=8(x-4) | | t^2+48t=0 | | (4x)=26 | | 7n^7+9n+5= | | 10.4+4= |

Equations solver categories